Pengaruh Kualitas Pelayanan, Disiplin Kerja Dan Kinerja Pegawai Kantor Desa Terhadap Kepuasan Masyarakat Pohgading Timur Kabupaten Lombok Timur - Irwan Hadi; I Made Suardana; I Made Murjana (Kredibel: Jurnal Ilmiah Manajemen, 2024)
This study aims to examine the effect of service quality, work discipline, and office employee performance on community satisfaction. So this study consists of 4 (four) variables, independent namely service quality (X1), work discipline (X2), employee performance (X3), and the dependent variable is community satisfaction (Y). the population of this study is the eastern pohgading community totaling 6,997 people, the criteria in this study are 15 years and over. The technique used in sampling is probability sampling with the simple ramdom sampling method and the number of respondents is determined as many as 98 respondents. This research was conducted by distributing questionnaires to 98 respondents of the East Pohgading community, East Lombok Regency. The results of this study indicate that the service quality variable has a significant effect on community satisfaction, the work discipline variable has no significant effect on community satisfaction, the employee performance variable has a significant effect on community satisfaction, and the simultaneous test results show that the independent variables (service quality, work discipline, and employee performance) have a significant effect on community satisfaction.